Design of digital-to-analogue signal converters for sensor microsystems on a crystal - Ilnytskyi, N.R.; Sorokhtey, T.R.; Umantsiv, V.M.; Pavlyuk, M.F.; Nykyruy, L.I.; Ilnytskyi, R.V. (Physics and Chemistry of Solid State, 2024)
The results of computer simulation of the developed R-2R digital-to-analogue converter design are given. Results with output voltage values for different digital input code are also given. The topology of such device is proposed, and its operation is modulated. Thus, the MicroWind software application was used to modelling and develop the operation of the digital signal to analogue converter, as it is an open-source software tool for all users, which allows the design and simulation of an integrated circuit at the physical description (IC) level.